Unravelling the Intricacies of Love and Hatred: A Comparative Analysis of the Classic ’Romeo and Juliet’ and Hashim Nadeem’s Contemporary Drama ’Khuda Aur Muhabbat Season 3’ - Hudda, Noor- ul -; Khaliq, Nosheen; Ghaffar, Faiza (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper aims to probe into the tragedy of two young lovers viewing the concept of exploration of love and hatred elements in Shakespeare’s play Romeo and Juliet and Hashim Nadeem’ s drama Khuda Aur Muhabbat (season 3). The study seeks to delve into the intricate tapestry of intricacies of love and hatred in both plays by unravelling its layers to reveal subtle patterns and underlying motifs. A strong theoretical foundation is established in the present study by incorporating feminist perspectives into the expedition of identity construction. Through a precise exploration of characters, settings, and narrative elements, the researcher carries out a thematic analysis, offering readers a comprehensive perspective that unveils the profound significance of hurdles in love. For the very purpose, this study utilizes purposive sampling technique to select a qualitative sample of five dialogues from two seminal works, investigating distinct cultural and temporal contexts. Finally the findings illuminate the persistent universality of pure love, sacrifice, and tragic consequences, resonating across Shakespeare's timeless classics and Hashim Nadeem's contemporary narratives.